How do professional teachers use cross-subject projects to develop students’ collaboration competence? - Indriani Ika Puspitasari; Suyatno; Enung Hasanah (Journal of Professional Teacher Education, 2026)
Collaboration is a crucial 21st-century competency that needs to be fostered through learning experiences offering students opportunities to work together to solve problems. This study aims to explore the development of students' collaboration competence through cross-subject projects. The research employs a qualitative approach with a case study design conducted at SMP Muhammadiyah 2 Yogyakarta, a Junior High School at Yogyakarta, Indonesia. Data were collected via observation, interviews, and documentation, and subsequently analyzed using the interactive analysis model developed by Miles, Huberman, and Saldana. The results indicate that collaboration competences were demonstrated at every stage of the cross-subject projects, ranging from theme selection, project planning, and scheduling to monitoring progress, assessment through project showcases, and experience evaluation. These competences were reflected in active engagement, positive communication, role distribution, responsibility, commitment to group goals, mutual assistance, and mutual respect. Project implementation was supported by teacher collaboration, integrated project modules, a conducive learning environment, and active student participation, although challenges remained regarding time constraints, limited communication, and uneven student participation. The findings imply that cross-subject projects can serve as a reference for teachers in designing integrated collaborative learning to facilitate the development of students' collaboration competence.